2003
DOI: 10.1179/026708303225009706
|View full text |Cite
|
Sign up to set email alerts
|

Phase characterisation and kinetic behaviour of diffusion soldered Cu/In/Cu interconnections

Abstract: The characterisation of diffusion soldered Cu/In/Cu interconnections is presented in this work. The main feature of this joining process is the production of a bond at a low fabrication temperature, which allows high service temperatures. The interconnection is formed entirely by intermetallic phases (IPs) which form isothermally rst by a liquid -solid reaction and then by a solid -solid reaction. The morphology and the growth kinetics of the IPs formed in the interconnection zone at temperatures in the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…14 for the present Ag-Sn-Ag system is different from the results reported for the interfacial reactions in the CuSn-Cu and Cu-InSn-Cu TLP systems with a time depen- dence of the form t 1/2 [15,24,25]. It is also different from the results reported for the coarsening kinetics of the Ni 3 Sn 4 scallops formed in the conventional Sn-based solder/Ni systems.…”
Section: Kinetics Of Ag 3 Sn Growthcontrasting
confidence: 85%
See 3 more Smart Citations
“…14 for the present Ag-Sn-Ag system is different from the results reported for the interfacial reactions in the CuSn-Cu and Cu-InSn-Cu TLP systems with a time depen- dence of the form t 1/2 [15,24,25]. It is also different from the results reported for the coarsening kinetics of the Ni 3 Sn 4 scallops formed in the conventional Sn-based solder/Ni systems.…”
Section: Kinetics Of Ag 3 Sn Growthcontrasting
confidence: 85%
“…(15) can then be applied to the correlation length g 0 values in Fig. 11b and an initial value of 18.2 lm for the as-reflowed Ag-Sn-Ag sample to analyse the radial growth kinetics of Ag 3 Sn:…”
Section: Kinetics Of Ag 3 Sn Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…For Ag-In interconnections bonded at 320°C for 280 min, Ag 9 In 4 firstly generated and transformed to Ag 3 In in 30 min. Sommadoosi [20] has found that Cu and In could react in different ways at different temperatures. Cu 11 In 9 firstly generates when the bonding temperature is below 310°C while Cu 2 In could generate firstly with higher temperature.…”
Section: Introductionmentioning
confidence: 99%